Thursday's children : a Frieda Klein mystery - French, Nicci (French, Nicci. Frieda Klein novel, 2016)
"The electrifying fourth book in the internationally bestselling Frieda Klein Mystery series. Drawn to brilliant and solitary London psychotherapist Frieda Klein, a growing readership is discovering Nicci French's acclaimed series with each chilling installment. In Thursday's Children, Frieda faces her most personal case yet when a former classmate appears at Frieda's door, begging for her help. Maddie Capel's teenage daughter, Becky, claims that she was raped in her own bed one night while her mother was downstairs. Her assailant warned, "Don't think of telling anyone, sweetheart. Nobody will believe you." Becky's story awakens dark memories of an eerily similar incident in Frieda's own past. When Becky is found hanging from a beam in her bedroom, Frieda sets out to find the man she believes is both her rapist and Becky's killer. But confronting the ghosts of the past turns out to be more dangerous than she ever expected"--